2015
DOI: 10.1182/blood-2014-07-590646
|View full text |Cite
|
Sign up to set email alerts
|

RNAi profiling of primary human AML cells identifies ROCK1 as a therapeutic target and nominates fasudil as an antileukemic drug

Abstract: Key Points• Large-scale loss-of-function RNAi screens in patientderived AML cells are feasible and able to pinpoint therapeutic targets.• ROCK1 inhibition exerts antileukemic effects in primary human AML cells in vitro and in vivo.Acute myeloid leukemia (AML) is characterized by a marked genetic heterogeneity, which complicates the development of novel therapeutics. The delineation of pathways essential within an individual patient's mutational background might overcome this limitation and facilitate personali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 49 publications
3
54
0
Order By: Relevance
“…A similar knock out experiment of PRR11 in hilar cholangiocarcinoma cell lines resulted in decreased cellular proliferation, migration, and tumor growth . WDHD1 is a key post-transcriptional regulator of centromeric, and consequently genomic, integrity (Hsieh et al, 2011) and its overexpression has been identified as biomarker of acute myeloid leukemia (Wermke et al, 2015), and lung and esophageal carcinomas (Sato et al, 2010). C15orf42 has been implicated in nasopharyngeal carcinoma .…”
Section: Discussionmentioning
confidence: 99%
“…A similar knock out experiment of PRR11 in hilar cholangiocarcinoma cell lines resulted in decreased cellular proliferation, migration, and tumor growth . WDHD1 is a key post-transcriptional regulator of centromeric, and consequently genomic, integrity (Hsieh et al, 2011) and its overexpression has been identified as biomarker of acute myeloid leukemia (Wermke et al, 2015), and lung and esophageal carcinomas (Sato et al, 2010). C15orf42 has been implicated in nasopharyngeal carcinoma .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, RNAi is widely used in the treatment of many diseases including amyloid disease, infectious diseases, myeloid leukemia, bone metabolic disorders, and so on. 21,[33][34][35] However, there is no available cartilage-specific targeting delivery system for siRNA delivery in the treatment of cartilage metabolic disorders, because cartilage is a relatively solid and compact tissue that is not easily penetrated by small molecules. In this study, we modified LNP, a positively charged siRNA delivery system, to specifically target articular cartilage, a negatively charged tissue, and to facilitate the delivery of therapeutic cargos to the chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the utility of the eZXM for drug screening, we studied the effects of the ROCK1 (Rho-associated coiled-coil protein kinase 1) inhibitor Fasudil in our model using leukemic tumor cells. As our colleagues have demonstrated that ROCK1 inhibition suppresses leukemic growth in-vitro and engraftment in a long-term murine xenotransplantation model 33 , we set out to study its effects in our in vivo set-up. We found that, compared to the untreated control embryos at 24 hpi (82.67 ± 11.02), Fasudil-treated embryos showed a significant reduction in tumor cell…”
Section: Rock-inhibition Inhibits Leukemic Cell Disseminationmentioning
confidence: 99%
“…Functional validation of the model was carried out using the Rock-inhibitor, Fasudil 33 . A working concentration of 50 µM Fasudil in water, prepared from 1 mM stock, also in water, was added to E3 medium containing injected embryos.…”
Section: Drug Treatment and Efficiency Evaluationmentioning
confidence: 99%